2007
DOI: 10.1159/000102584
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Virological Response in the Antiviral Therapy of Chronic Hepatitis C: Is There a Predictive Value of Interferon-Induced Depression?

Abstract: Background: The study objective was to determine the contribution of cytokine-induced depression to a predictive model of sustained virological response (SVR) in chronic hepatitis C. Methods: One hundred and one therapy-naïve hepatitis C virus (HCV) outpatients received treatment with peginterferon alfa-2b and ribavirin. Neuropsychiatric side effects were monitored prospectively (Hospital Anxiety and Depression Scale, DSM-IV criteria for major depression). SVR was defined as a failure to detect HCV by PCR 24 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…They hypothesize that optimal dosing of IFN-a could be associated with both the development of depression and higher response rates [27]. Similar to the findings in the studies by Castéra et al and Schä fer et al, in our study no association at all was found between effect of antiviral therapy and depression [15,28].…”
Section: Variablesupporting
confidence: 91%
See 1 more Smart Citation
“…They hypothesize that optimal dosing of IFN-a could be associated with both the development of depression and higher response rates [27]. Similar to the findings in the studies by Castéra et al and Schä fer et al, in our study no association at all was found between effect of antiviral therapy and depression [15,28].…”
Section: Variablesupporting
confidence: 91%
“…Similar to the findings in the studies by Castéra et al. and Schäfer et al ., in our study no association at all was found between effect of antiviral therapy and depression [15,28].…”
Section: Discussionmentioning
confidence: 70%
“…Kraus, et al [26] and Schaefer, et al similarly reported that preventative administration of SSRI before starting interferon treatment it was effective in patients with depression or a history of depression. Schafer, et al [27] reported no relation between the SVR rate and the development of depression. Loftis, et al [28] reported that major depressive disorder induced interferon-α might be a predictor of a positive response to interferon-α therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, psychiatric examinations may be impossible in some cases due to a lack of psychiatric clinics or cost performance issues. In such cases, the Hamilton Rating Scale for Depression, and the Montgomery-Asberg Depression Rating Scale (MADRS) [29] may be useful as clinician rated scales, or the Zung Self-rating Depression Scale [27], Beck's Depression Inventory (BDI) [30], and Hospital Anxiety and Depression Scale (HADS) [31] may be useful as self-rating scales to evaluate the risk of psychiatric disorders. In this study, the SVR rate was not significantly higher in the pre-treatment group (Group A) than in the non pretreatment group (Group B).…”
Section: Discussionmentioning
confidence: 99%
“…Although, there are limitations of experimentation in mouse models with regard to the applicability of findings to human JEV infection, this is a widely accepted methodology to evaluate new antiviral compounds. Indeed, interferon-α, a known antiviral agent shown to be effective in vitro and in vivo in animal models against JEV, has been assessed in open human trials with encouraging results [19,20,21]. Since mycophenolic acid is already in clinical use for transplant patients [22], it may qualify as a candidate drug for evaluation in JEV infections.…”
Section: Discussionmentioning
confidence: 99%